Pengaruh Komposisi Asam Bis(2-Etilheksil)Fosfat (D2EHPA) dan Tributil Fosfat (TBP) dalam Resin Amberlite Xad-16 terhadap Sorpsion-Ion La(III), Nd(III) dan Gd(III) - Ibnu Khaldun; Buchari Buchari; Muhammad Bachri Amran; Aminudin Sulaeman (Jurnal Matematika & Sains, 2009)
Sorption of La(III), Nd(III), and Gd(III) ions with solven-timpregnated resins using bis(2-ethylhexyl)phosphoric acid (D2EHPA) and tributhylphosphate (TBP) as extractants and Amberlite XAD-16 as a polymeric support has been studied. The impregnated resins containing various amounts of extractants have been prepared by the wet and dry methods. The effects of pH, types, of extractant, extractant content (extractants/resin ratios of 10/90, 20/80, 50/50, 60/40 wt.%) and contact time on sorption of those metalic ions have been investigated by batch method. The sorption capacity of Amberlite XAD-16 resin previously prepared by the wet method with a 60/40 extractant/resin mass ratio for TBP, D2EHPA/TBP, and D2EHPA were 104.3 mg/g, 99.1 mg/g and 86.2 mg/g resin, respectively. Meanwhile, sorption capacity of Amberlite XAD-16 resin previously prepared by dry method was found to be 645 mg/g; 419.16 mg/g, and 386.9 mg/g resin, respectively. The sorption percentage of the studied metal ions was within the range of 90- 99% for TBP, D2EHPA/TBP and D2EHPA XAD-16 resins at 20/80 extractant/resin mass ratio.